Expanding Prospects for Dermal Health with Bioactive Phytochemicals - Garg, Ishu; Singh, Neelam; Neha3; Harish1; Barman, Moumita; Gupta, Puneet; Sharma, Manoj (Recent Advances in Inflammation & Allergy Drug Discovery, 2025)
The largest and most defensive organ in the human body is the skin. Skin health significantly affects the quality of life due to its crucial function in aesthetic appearance. The onset of numerous skin illnesses is frequently accompanied by chronic skin inflammation. Immune-mediated reactions defend the body against external harm and need to be quickly controlled. If unregulated, they can result in long-term cellular damage and a variety of skin diseases. Dermatological illnesses encompass a wide range of skin conditions, including but not limited to acne, eczema, psoriasis, vitiligo, dermatitis, skin cancer, and fungal infections. Phytochemicals are produced by plants as a defense mechanism against pathogens that have various biological activities and can be harnessed for therapeutic purposes. Through the quenching of free radicals and the suppression of nuclear factor-κB, phytochemicals shield the skin from damage. Phytochemicals also offer a safe topical delivery system for improving the skin and regenerative treatment. Some phytochemicals' direct molecular targets have been identified, and their underlying mechanisms of action are being researched. In this review, we summarise current studies on phytochemicals' impacts on dermal illnesses and their underlying mechanisms of action.
Keywords: skin regeneration